NEK1 mutations in familial amyotrophic lateral sclerosis: letter to the editor - Brenner, David; Müller, Kathrin; Wieland, Thomas; Weydt, Patrick; Böhm, Sarah; Lulé, Dorothée; Hübers, Annemarie; Neuwirth, Christoph; Weber, Markus; Borck, Guntram; Wahlqvist, Magnus; Danzer, Karin M.; et al. (Brain, 2016)
Sir, Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by adult-onset loss of motor neurons. Five to 10% of all ALS cases are familial ALS. To date, more than 20 genes have been implicated in causing familial ALS, with the discovery of mutations in CHCHD10 ( Bannwarth et al. , 2014 ) and TBK1 ( Cirulli et al. , 2015 ; Freischmidt et al. , 2015 ) representing the latest examples for monogenic causes of ALS. Most recently, whole exome sequencing of ALS patients suggested an association of heterozygous loss-of-function mutations in NEK1 with ALS. However, this observation was made in a cohort of mostly sporadic patients, and the result was only significant in a combined analysis of the discovery and the replication cohort ( Cirulli et al. , 2015 ), making further validation essential.